Uma proposta de sequência didática para o ensino de eletrólise na educação básica - Martins, Ana Laura da Silva (2017)
The present study presents a research on the teaching of Electrolysis in basic education through the didactic sequence. The general objective was to develop a didactic sequence that would help the Chemistry teacher in the planning of chemical concepts, specifically in the teaching of Electrolysis. Thus, motivated by references that highlight the critical and intentional use of experimentation, we elaborated a didactic guide with activities ordered from experimental activities for the teaching of Electrolysis, so that auxiliary teachers without the development of classes in education. The proposed methodology aims to contribute to the pedagogical practice of teachers without experimental teaching of Chemistry in order to contemplate an innovative approach, contextualized and easy to apply in class. With these pretensions we start first for a bibliographical research on the subject in didactic books and published researches New Chemical Comparison in the school (QNesc), more specifically in the section "Experimentation in Chemistry Teaching" and dissertation and thesis bank of the Coordination of Personal Improvement of Higher Education (CAPES). In this sense, we also investigated an approach to the concept of electrolysis in the experimental activities of Didactic Chemistry Books (LDQs) approved in the 2015 National Textbook Program (PNLD-2015). From this, the following problem is proposed: What contributions of the didactic guide for the teaching of electrolysis in the pedagogical practice of chemistry teachers in basic education? In terms of structure, detachments on the internet, we present a brief reflection on the learning process advocated by Vygotsky to value the dynamic-interactive practice. The studies indicate that as experimental activities favor the learning of chemical concepts and are relevant for teaching and learning, using alternative materials and experimental kit. The results obtained in this investigation attest that the research subjects approved the educational and teaching product without educational potential when informed that it is a program to prepare and improve the quality of teaching. It is possible to affirm that the methodology used makes the educational product validated for the teaching of Electrolysis and that the technical and pedagogical aspects of this will make a significant contribution to quality teaching and training of more active students.